Predictors associated with clinical improvement of SARS-CoV-2 pneumonia. Issue 6 (June 2021) - Mitsumura, Takahiro; Okamoto, Tsukasa; Shirai, Tsuyoshi; Iijima, Yuki; Sakakibara, Rie; Honda, Takayuki; Ishizuka, Masahiro; Aiboshi, Junichi; Tateishi, Tomoya; Tamaoka, Meiyo; Shigemitsu, Hidenobu; Arai, Hirokuni; et al.
Abstract: Background: There are few agents that have been proven effective for COVID-19. Predicting clinical improvement as well as mortality or severity is very important. Objectives: This study aimed to investigate the factors associated with the clinical improvement of COVID-19. Methods: Overall, 74 patients receiving treatment for COVID-19 at Tokyo Medical and Dental University Hospital from April 6th to May 15th, 2020 were included in this study. Clinical improvement was evaluated, which defined as the decline of two levels on a six-point ordinal scale of clinical status or discharge alive from the hospital within 28 days after admission. The clinical courses were particularly investigated and the factors related to time to clinical improvement were analyzed with the log-rank test and the Cox proportional hazard model. Results: Forty-nine patients required oxygen support during hospitalization, 22 patients required invasive mechanical ventilation, and 5 patients required extracorporeal membrane oxygenation. A total of 83% of cases reached clinical improvement. Longer period of time from onset to admission (≥10 days) (HR, 1.057; 95% CI, 1.002–1.114), no hypertension (HR, 2.077; 95% CI, 1.006–4.287), and low D-dimer levels (<1 μg/ml) (HR, 2.372; 95% CI, 1.229–4.576) were confirmed to be significant predictive factors for time to clinical improvement. Furthermore, a lower SARS-CoV-2 RNA copy number was also a predictive factor for clinical improvement. Conclusions: Several predictors for the clinical improvement of COVID-19 pneumonia were identified. These results may be important for the management of COVID-19 pneumonia.